A visually detectable pH responsive zirconium metal–organic framework. Issue 16 (2nd February 2016) - Moon, Su-Young; Howarth, Ashlee J.; Wang, Timothy; Vermeulen, Nicolaas A.; Hupp, Joseph T.; Farha, Omar K.
Abstract : A functionalized MOF, NU-1000–CNF, shows simultaneous hydrolysis of nerve agent simulants while visually sensing the acid byproducts produced. Abstract : A halochromic Zr6 -based metal–organic framework is synthesized using solvent-assisted linker incorporation (SALI) with NU-1000 as a platform and carboxylnaphthofluorescein as a pH sensitive ligand. The functionalized MOF can catalytically detoxify nerve agent simulants in addition to visually detecting the acidic byproduct produced during detoxification.